The usage of online payment transactions during the COVID-19 pandemic / Ramli Saad ... [et al.] - Saad, Ramli; Wan Mahamad, Wan Shahrul Aziah; Mahshar, Mursyda (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Due to the COVID-19 pandemic's lockdown and store closures in Malaysia, many people turn to online and mobile shopping for groceries, daily essentials, and other products. The pandemic is changing not only how people shop, but also how they pay for their purchases. In order to maintain a social distance from one another, most people will choose to pay by utilising an online payment option. Through online payment, people, particularly customers, can pay for goods or services that they buy from anywhere and at any time. Furthermore, online payments have aided economies in continuing to operate even during times of lockdown, as well as gaining from the shift to cashless transactions and online shopping (Latta, & Sarkar, 2021). The COVID-19 pandemic has had a tremendous impact on the payment industry as a whole. Only a few sectors have benefited, while the remainders have suffered severe consequences. After analysing COVID-19's influence across all payment sectors, one thing is clear that if a firm wants to survive during the pandemic, it must implement digital payment methods (Redjeki, & Affandi, 2021). They must provide a simple, convenient, and socially distancing-friendly form of selection to their customers. People can now use a variety of online payment methods, including credit or debit card payments, bank transfers, e-wallet, and mobile payments. Thus, this paper intends to highlight the usage of online payment transactions during the pandemic.